Electromyography of shoulder muscles in individuals without scapular dyskinesis during closed kinetic chain exercises on stable and unstable surfaces: a systematic review and meta-analysis - Ramin Arghadeh; Mohammad Hossein Alizadeh; Hooman Minoonejad; Rahman Sheikhhoseini; Mojtaba Asgari; Thomas Jaitner (Frontiers Media S.A., 2024)
IntroductionUnstable surfaces are commonly utilized to enhance the flexibility of the musculoskeletal system for achieving training or rehabilitation goals. However, their effects on shoulder muscle activation during various push-up (PU) exercises have not been thoroughly investigated. Therefore, the purpose of this study was to synthesize electromyography (EMG) data of shoulder muscles in individuals without scapular dyskinesis performing different PU exercises on both stable and unstable surfaces.MethodsA systematic online search was conducted in electronic databases, including Web of Science, PubMed, Scopus, and Google Scholar, up to January 16, 2024, using predefined sets of keywords. Out of the 1,971 titles and abstracts screened, 80 articles were reviewed in detail by two independent researchers to check the eligibility, of which 28 eligible studies were ultimately included. Following assessment of the quality and risk of bias, the studies were categorized based on exercises and muscle groups, and a meta-analysis using a random-effects model was performed to estimate the overall effect size.ResultsThe use of unstable surfaces led to a decrease in anterior deltoid activity during PU [P = 0.032; I2 = 91.34%; SMD = −0.630 (95% CI −1.205, −0.055)], an increase in pectoralis major activity during PU [P = 0.006; I2 = 63.72%; SMD = 0.282 (95% CI 0.079, 0.484)], as well as during knee PU [P = 0.018; I2 = 32.29%; SMD = 0.309 (95% CI 0.052, 0.565)], and an increase in triceps brachii activity during PU [P = 0.000; I2 = 85.05%; SMD = 0.813 (95% CI 0.457, 1.168)], knee PU [P = 0.000; I2 = 0.00%; SMD = 0.589 (95% CI 0.288, 0.891)], as well as during push-up plus [P = 0.006; I2 = 13.16%; SMD = 0.563 (95% CI 0.161, 0.965)]. However, the use of unstable surfaces did not show a significant effect on the EMG activity of the pectoralis major during push-up plus [P = 0.312; I2 = 22.82%; SMD = 0.207 (95% CI −0.194, 0.609)].ConclusionsUnstable surfaces can modulate muscle activity in different PU exercises, while the effects on the targeted muscles depend on the type of exercise. The findings of this review provide a framework based on the level of activity of each shoulder muscle during different PU exercises, which can help coaches, trainers, and sports therapists select the most suitable type of PU for designing training or rehabilitation programs. Particularly, the most suitable exercise for increasing anterior deltoid activity is PU on a stable surface. To concurrently increase activity of the pectoralis major and triceps brachii, adding unstable surfaces under hands during knee PU and standard PU is recommended.Systematic Review RegistrationPROSPERO, identifier CRD42021268465.